Gender-Based Violence against Women in Intimate and Couple Relationships. The Case of Spain and Italy during the COVID-19 Pandemic Lockdown - Donato, Stellamarina (Italian Sociological Review, 2020)
This article addresses the issue of gender-based violence against women (GBVAW) during the COVID-19 pandemic lockdown. With an emphasis on intimate partner violence (IPV), it focuses on the degree of government responsiveness to this issue and compares the cases of Spain and Italy: two European countries that – from March to May 2020 – were among the hardest hit during the coronavirus pandemic. The aim of this paper is twofold: to investigate how the two nation-states dealt with violence against women (VAW) during the pandemic – which mostly refers to intimate and couple relationships – and to compare their different degrees of government responsiveness in this specific section of progressive social policies. While COVID-19 was spreading, the country ruled by Prime Minister Pedro Sánchez proved to be very active in advancing practical guidelines and measures to deal with GBVAW, whereas Italy, governed by Prime Minister Giuseppe Conte, didn’t act likewise. The article adopts a multi-method approach and argues that the way a specific society presents a social phenomenon influences its response in terms of policies. Furthermore, this investigation claims that the dialogue between civil society and the institutional level needs to be reinvigorated in order to comprehensively address GBVAW. Perhaps, by presenting a comparison between similar cases in a situation of emergency, this article could serve this aim.